TRADITIONAL KNOWLEDGE AND SUSTAINABLE DEVELOPMENT - Manjari Chandra; Shabran, Rohit P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper looks at how IP laws have attempted to safeguard conventional knowledge and how it may be stolen. Although traditional knowledge is protected by the Biodiversity Act, there have been cases of bio-piracy involving traditional medical knowledge and the usage of plants to treat a range of illnesses. The author will explain the need to preserve traditional knowledge and the idea of bio-piracy using the three well-known Indian examples of neem, turmeric, and basmati rice. In addition, I'll investigate whether there are any constitutional protections for sacred traditional knowledge. To preserve TK, several international agreements have been put into effect. Global issues including food security, environmental degradation, and sustainable livelihoods can be addressed by combining traditional knowledge with contemporary scientific methods. The role of traditional knowledge in intellectual property protection has been a hot topic of debate ever since the 1992 Convention on Biological Diversity and the 1995 TRIPS agreement. A single solution is unlikely to be able to address the vast array of issues and goals related to TK protection. Since TK is essential to the existence of many indigenous people, care should be made to protect it. With a focus on its applicability to accomplishing the Sustainable Development Goals of the UN, this article examines the complementary relationship between traditional knowledge and sustainable development. While a complete sui generis legal framework is being developed, traditional knowledge can be secured by utilizing already-existing forms of intellectual property or by combining multiple different types of IP.